Potassium Dynamic and Availability from Composted and Uncomposted Rice Straw - Mulyadi (2000)
Managing rice straw (in term of K source) is essential if sustainability is to be achieved with a small amount of inorganic K fertilizer. About 80 % K taken up by rice crop (Oryza sativa L.) is in the straw. To increase efficiency of K utilization from the rice straw, it is essential to know the K supplying characteristic and crop available K from the straw. Information of this kind may also help in a better understanding of K cycling in soil--crop system. Two experiments were conducted in a glasshouse. The first experiment, composting of rice straw, was to study the changes in tensile load of rice straw during rice straw composting, its possibility as an indicator for the state of decomposition and K released. The second experiment, a pot experiment using com (Zea mays L.) variety of PJ-58 as test crop for K uptake planted on Bungor series soil (Typic PaleuduJt), was firstly to evaluate the crop available K from composted (CRS) and uncomposted (UCRS) rice straw compared to that from Muriate of Potash (MOP) as standard K fertilizer and secondly to evaluate the use of tensile load of rice straw as an indicator to predict K released from UCRS incorporated in the soil, the crop K uptake and leaf K concentration. The results indicated that during composting of rice straw, the individual relationships between the percentage of organic matter remaining, the contents of total and water soluble K of decomposing rice straw with the tensile load of indicator rice straw are highly significant (P :s 0.01) with linear correlation coefficients of 0.97, - 0.96 and - 0.94, respectively. Therefore, tensile load of indicator rice straw can possibly be used as an alternative indicator for the state of decomposition of rice straw and to predict K released. Applications of MOP, CRS and VCRS to the soil increased K accumulated in com crop, total and exchangeable K contents of the soil, but their increase depends on the crop growth period, the K rate and availability of fertilizer applied. Compared to MOP and VCRS, the use of CRS is more beneficial in increasing the crop K, P and ea uptake and results in better crop growth. As a source of K, the K availability from CRS was more readily available than that from UCRS and MOP; however at 56 days after planting (tasseling stage) and a rate of 3 60 mg K porI (90 kg K ha-I), the crop available (uptake) K from the three K fertilizer sources were similar, ranging from 90.48 to 109.25 %. Tensile load of indicator rice straw can also possibly be used as indicator to predict K released from UCRS incorporated into the soil based on the correlation of tensile load and K content in the decomposing rice straw during composting. The trends are less applicable as indicator to predict the crop K uptake and leaf K concentration of com.